ASI dan MP-ASI “Optimalisasi Pertumbuhan Anak Melalui Pelatihan Mengolah Dan Menerapkan Pola Pemberian MP-ASI”.: ASI dan MP-ASI - septiani, winda; Nurhapipa, Nurhapipa; Kartilian, Felianda (Jurnal Pengabdian Kesehatan Komunitas (Journal of Community Health Service), 2023)
Complementary Foods for Mother's Milk (MP-ASI) are foods that contain nutrients that are given to children aged more than 6 months to meet the nutritional intake needs other than breast milk. Mother's milk (ASI) is only able to meet 2/3 of the nutritional intake needs of children at the age of 6-9 months and at the age of 9-12 months, breast milk is only able to meet 1/2 of the nutritional intake needs of children. The purpose of this service is to pursue increasing children's weight gain through training to process MP-ASI and apply the pattern of giving MP-ASI properly. The target of this service is mothers who have toddlers (6-24 months) who reach 10 toddlers which are carried out from April to June 2022 at Posyandu RW 10 Puskesmas Harapan Raya. This activity includes several stages, namely the data collection stage, filling out the prepost to the mother of toddlers, measuring the child's initial/late weight, providing counseling and demonstration of MPASI. The final result of the evaluation of parents' knowledge about breastfeeding and complementary feeding showed a significant value before and before the intervention was given by obtaining p = 0.000, meaning that there was a significant change in the score of mother's knowledge before and before the intervention. also with the child's weight there is a significant effect on the child's weight before and before the intervention is given with the acquisition of p = 0.000. Nutrition education/education about breastfeeding and complementary feeding can increase parental knowledge so that it can become the basis for parents to take action so that children can avoid nutritional problems and have maximum development and growth. Abstrak Makanan Pendamping Air Susu Ibu (MP-ASI) adalah makanan yang mengandung zat gizi yang diberikan kepada anak berusia lebih dari 6 bulan untuk memenuhi kebutuhan asupan gizi selain Air Susu Ibu. Air Susu Ibu (ASI) hanya mampu memenuhi 2/3 dari kebutuhan asupan gizi anak pada usia 6-9 bulan dan pada usia 9-12 bulan ASI hanya mampu memenuhi 1/2 dari kebutuhan asupan gizi anak. Tujuan dari kegiatan pengabdian ini adalah untuk mengejar percepatan kenaikan berat badan anak melalui pelatihan mengolah MP-ASI dan menerapkan pola pemberian MP-ASI dengan baik. Sasaran pengabdian ini adalah ibu yang memiliki balita (6-24 bulan) yang berjumlah 10 orang balita yang dilakukan pada bulan april hingga bulan Juni tahun 2022 di Posyandu RW 10 Puskesmas Harapan Raya. Kegiatan ini meliputi beberapa tahapan yaitu tahap pendataan, pengisian prepost kepada ibu balita, pengukuran BB awal/akhir anak, pemberian penyuluhan dan demo MPASI. Hasil pengabdian diperoleh evaluasi pengetahuan orang tua tentang ASI dan MPASI menunjukkan nilai yang signifikan sebelum dan sesudah diberikan intervensi dengan peroleh p=0,000 artinya ada perubahan signikan skor pengetahuan ibu sebelum dan sesudah intervensi. Begitu juga dengan berat badan anak ada pengaruh yang signifikan berat badan anak sebelum dan sesudah diberikan intervensi dengan perolehan p=0,000. Pendidikan/Edukasi gizi tentang ASI dan MP-ASI dapat meningkatkan pengetahuan orang tua sehingga dapat menjadi dasar bagi orang tua untuk melakukan tindakan agar anak dapat terhindar dari masalah gizi dan memiliki perkembangan serta pertumbuhan yang maksimal.